PENGARUH PELATIHAN HATHA YOGA TERHADAP JOB BURNOUT: MASA KERJA SEBAGAI KOVARIABEL - , Willi Brordus Nugraha Adhi Bhratta ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Job burnout caused absentism, turnover, physical illness and depression to the nurses. This matter had an implication toward the low quality of service to the patients and the low productiveness of the organization. In relation to the situation, the research objetive was to find the influence of hatha yoga training toward the job burnout with the job tenure as the co-variable. The research hypothesis was that there had been a significant difference between the experimental group and the control group after the hatha yoga training. The job burnout level in the experimental group were lower than that of the control group. The working period as a co-variable had a significant contribution toward the decrease of job burnout. The researcher employed experimental approach by means of pre-test and post-test control group design as the research method. The subjects of the research were 14 nurses of Bhayangkara Yogyakarta Hospital divided randomly in the experimental group (n = 5) and in the control group (n = 9). The researcher employed ancova, Mann-Whitney and mixed anova for the data analysis technique. The results of the research hypothesis test was that there had been a significant difference between the experimental group and the control group after the hatha yoga training (F = 21.437